SIMBOLISME-RELIGIUS SYAIR KESENIAN COWONG - Arif Hidayat (IBDA` : Jurnal Kajian Islam dan Budaya, 2011)
This article discusses the religious symbolism contained in the lyric of Cowong arts. Interpretation of the symbol refers to Ricoeur thought as reading strategies. Language in the Cowong art poem recited in the middle-Javanese language, that asking the Creator for the coming rain. It’s very unique cycle with tracing the hydrological cycle, but the procedure for disclosure of poetry is the prayers that are being said to the Creator. Those prayers believed as granted revelation of rain after the ritual is done.